2020
DOI: 10.1371/journal.pone.0228756
|View full text |Cite
|
Sign up to set email alerts
|

Effect of restricting bedtime mobile phone use on sleep, arousal, mood, and working memory: A randomized pilot trial

Abstract: BackgroundThis study aimed to assess the effects of restricting mobile phone use before bedtime on sleep, pre-sleep arousal, mood, and working memory. MethodsThirty-eight participants were randomized to either an intervention group (n = 19), where members were instructed to avoid using their mobile phone 30 minutes before bedtime, or a control group (n = 19), where the participants were given no such instructions. Sleep habit, sleep quality, pre-sleep arousal and mood were measured using the sleep diary, the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 33 publications
1
46
0
Order By: Relevance
“…Following previous studies (22)(23)(24), the present work also estimated age, gender, socioeconomic status (marital status, occupation, and education), and health habits (smoking, alcohol consumption, hours sleeping, and time exposed to screens). In addition, other variables concerning the confinement context were also controlled: number of days isolated because of COVID-19 confinement, whether participants were living alone during COVID-19 confinement, and, last, whether they were exposed or infected with COVID-19.…”
Section: Covariatesmentioning
confidence: 99%
“…Following previous studies (22)(23)(24), the present work also estimated age, gender, socioeconomic status (marital status, occupation, and education), and health habits (smoking, alcohol consumption, hours sleeping, and time exposed to screens). In addition, other variables concerning the confinement context were also controlled: number of days isolated because of COVID-19 confinement, whether participants were living alone during COVID-19 confinement, and, last, whether they were exposed or infected with COVID-19.…”
Section: Covariatesmentioning
confidence: 99%
“…The few existing experimental studies that have been conducted report contradictory results on sleep measures [ 19 , 29 - 31 ]. For instance, restricting mobile phone use before bedtime for 4 weeks had no effect on sleep measures in a study conducted by Harris el al [ 29 ] in Norwegian high school athletes, while He et al [ 30 ] found several improvements in both sleep measures and working memory in Japanese university students. Of note, the inclusion criteria differed in the 2 studies: He et al [ 30 ] only included participants with poor sleep and a habit of using a mobile phone during bedtime, while Harris et al [ 29 ] did not have such inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, restricting mobile phone use before bedtime for 4 weeks had no effect on sleep measures in a study conducted by Harris el al [ 29 ] in Norwegian high school athletes, while He et al [ 30 ] found several improvements in both sleep measures and working memory in Japanese university students. Of note, the inclusion criteria differed in the 2 studies: He et al [ 30 ] only included participants with poor sleep and a habit of using a mobile phone during bedtime, while Harris et al [ 29 ] did not have such inclusion criteria. In our feasibility study, we did not have any inclusion criteria regarding smartphone use meaning that we included both light and heavy smartphone users.…”
Section: Discussionmentioning
confidence: 99%
“…The N refers to how many trials back they have to refer to, with difficulty increasing with each higher N. VGPs demonstrated increased task performance on the 1-Back and 2-Back trials, respectively, suggesting increased working memory performance compared to NVGPs. The N-Back task was also used by He et al (2020) to assess the impact of restricted mobile phone use prior to sleep. Participants completed baseline measurements before being divided into two groups.…”
Section: Working Memorymentioning
confidence: 99%